Method for inhibiting sintering distortion of cemented carbide

CN122999987APending Publication Date: 2026-10-30CHONGYI ZHANGYUAN TUNGSTEN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611512110.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-28
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0016]本申请提出了一种抑制薄片类硬质合金烧结变形的方法,产生了如下有益效果:通过将冷冻后的硬质合金压坯转移至特定湿度下吸水附氧形成薄氧化层,有助于减少烧结时压坯表面与内部因碳含量差异导致的收缩不同步;通过压条约束压坯变形面,改善烧结后该面变形情况;通过压条约束与压坯表面吸水附氧在烧结时的协同作用,减少薄片类硬质合金的变形。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999987A_ABST
    Figure CN122999987A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of hard alloy, and particularly relates to a method for inhibiting sintering deformation of thin hard alloy, which comprises the following steps: obtaining hard alloy compacts according to predetermined sizes, and freezing the hard alloy compacts; transferring the frozen hard alloy compacts to an environment with room temperature and humidity greater than or equal to 50% for pretreatment for 10-60 min; placing the pretreated hard alloy compacts in a groove-shaped boat, and fixing the hard alloy compacts by using a pressing strip, and then sintering to obtain hard alloy thin sheets. The method can help to reduce the asynchronous shrinkage of the surface and the interior of the compacts due to the difference in carbon content during sintering by transferring the frozen hard alloy compacts to a specific humidity to absorb water and attach oxygen to form a thin oxide layer; the deformation of the surface of the compacts can be improved after sintering by using the pressing strip to constrain the deformation surface; and the deformation of the thin hard alloy can be reduced by the synergistic effect of the constraint of the pressing strip and the water absorption and oxygen attachment on the surface of the compacts during sintering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of cemented carbide technology, specifically a method for suppressing sintering deformation of thin-film cemented carbide. Background Technology

[0002] Thin-film cemented carbide, with its high hardness, wear resistance, corrosion resistance, and excellent high-temperature stability, is widely used as a key component or basic material in many fields of modern industry. In machining and mold making, it is used to manufacture cutting tools such as lathe and milling cutters, as well as inserts and wear-resistant liners for precision molds. In the paper packaging, printing, and textile industries, it is commonly found in corrugated paper slitting blades, printing machinery scraper blades, and textile machinery yarn guides. Furthermore, in the electronics and semiconductor fields, it is used to manufacture vacuum coating components, electronic component molds, and circuit board drilling guides. In resource extraction, it is used to manufacture wear-resistant parts such as rock drill bits and cutting teeth. It is also used to manufacture wear-resistant and corrosion-resistant components such as valve sealing linings and chemical corrosion-resistant liners.

[0003] During the production process, because thin-film cemented carbide has the characteristics of small thickness and large planar area, it is easily deformed during the sintering stage due to the uneven density of the compact and the sintering atmosphere. This reduces the dimensional accuracy of the thin-film cemented carbide, increases the grinding cost of subsequent processing, and reduces the final yield. Summary of the Invention

[0004] To address the aforementioned problems, this application provides a method for suppressing sintering deformation of thin-sheet cemented carbide. This method involves freezing the thin-sheet cemented carbide blank at a low temperature, then transferring it to specific conditions for slight surface oxygenation. Subsequently, during sintering, a pressure bar is used to constrain the deformation surface of the blank, thereby suppressing sintering deformation of the thin-sheet cemented carbide and improving the yield rate of the thin-sheet cemented carbide.

[0005] This application discloses a method for suppressing sintering deformation of thin-film cemented carbide, comprising the following steps: S1. Obtain a cemented carbide blank according to a predetermined size, and freeze the cemented carbide blank; S2. Transfer the frozen cemented carbide billet to an environment with room temperature and humidity ≥50% for pretreatment for 10~60min; S3. The pretreated cemented carbide blank is placed in a trough-shaped boat and fixed with a pressure bar, and then sintered to obtain a cemented carbide sheet.

[0006] In the above technical solution, in step S1, the cemented carbide blank is frozen as a whole to provide temperature conditions for subsequent surface oxygen application to the blank. In step S2, the frozen cemented carbide billet is transferred to an environment with room temperature and humidity ≥50%. At this time, the air contains a large amount of water molecules, while the frozen billet itself is at a low temperature. Water molecules will adhere evenly to the surface of the billet through condensation, causing the surface to absorb water and oxygen, thus forming a thin oxide layer. During sintering, the carbon atmosphere in the furnace reacts with this oxide layer to generate carbon monoxide, thereby consuming some of the oxygen on the surface. This process helps to reduce the asynchronous shrinkage between the surface and the interior of the billet caused by the difference in carbon content. By controlling the placement time of the frozen cemented carbide billet in an environment with room temperature and humidity ≥50% within the range of 10~60 minutes, oxygen can be attached to the surface while the overall oxidation content is controlled within the acceptable range, which will not affect the product performance during sintering. If the time is too long, the surface of the billet will easily absorb excessive water, resulting in excessive oxygen on the product surface. During sintering, the excessive oxygen reacts with the carbon in the billet itself, which can easily cause decarburization and unacceptable performance. If the time is too short, the absorption of water and oxygen will be insufficient, which cannot offset the difference in carbon content between the surface and the interior of the billet, resulting in deformation. In step S3, compared to the product bearing force on one side of the flat boat, the product can be placed on both sides in the trough-shaped boat, and both sides can be constrained to be flat during sintering shrinkage. The pressure strip is used to completely cover the filling surface during the pressing of the compact to fix the compact. The pressure strip will flatten the filling surface of the compact through its own weight during the sintering shrinkage process, reducing the impact of uneven material distribution caused by the back-and-forth movement of the material shoe during the pressing process, thereby reducing the occurrence of deformation and warping problems and improving the deformation of the surface after sintering.

[0007] Furthermore, the predetermined dimensions are 10-300mm in length, 10-80mm in width, and 2-15mm in height.

[0008] Furthermore, in step S1, the cemented carbide blank is placed in an environment of -10~-30℃ and humidity ≤30% for freezing; This low-temperature drying environment facilitates long-term storage of cemented carbide blanks, preventing the surface of the blanks from oxidizing in a short time and affecting the overall carbon content of the product. At the same time, this environment can lower the overall temperature of the blanks to below -10℃, which helps with subsequent water absorption and oxygen adsorption.

[0009] Furthermore, the sintering temperature is 1420~1440℃ and the time is 40~60min.

[0010] Furthermore, the length, width, and height of the cemented carbide blank are 1.21 to 1.26 times the length, width, and height of the predetermined dimensions, respectively.

[0011] Furthermore, the trough-shaped vessel is a V-shaped trough-shaped vessel.

[0012] Furthermore, the pressing strip is a graphite strip prepared by cold isostatic pressing, and the surface of the pressing strip is coated with a sprayed coating. Graphite strips prepared by cold isostatic pressing have high density and low porosity, making them less likely to carry impurity elements that affect the alloy's properties. Furthermore, the contact surface between the pressing strip and the blank is coated with a sprayed layer, thus preventing adhesion and carburization and avoiding any impact on the alloy's properties.

[0013] Furthermore, the mass of the pressure strip is 20% to 40% of the mass of the cemented carbide blank, so as to provide sufficient constraint on the cemented carbide blank without causing the cemented carbide blank to bend during the sintering process due to excessive weight.

[0014] Furthermore, the cemented carbide sheet comprises 4wt% to 12wt% Co, with the balance being WC, additives, and unavoidable impurities.

[0015] Furthermore, the cemented carbide sheet is considered qualified if it meets the following characteristics: The difference between the length, width, and height of the cemented carbide sheet and the predetermined dimensions does not exceed 0.5 mm, and each surface, when measured with a plug gauge, does not exhibit bending greater than 0.3 mm; the cobalt magnetism of the cemented carbide sheet is 3%~10.5%, the magnetic force is 10~45 KA / m, and decarburization does not occur; The pass rate of the cemented carbide sheets shall not be less than 98%.

[0016] This application proposes a method to suppress sintering deformation of thin-film cemented carbide, which produces the following beneficial effects: by transferring the frozen cemented carbide blank to a specific humidity level to absorb water and oxygen to form a thin oxide layer, it helps to reduce the asynchronous shrinkage between the surface and interior of the blank due to the difference in carbon content during sintering; by constraining the deformation surface of the blank with a pressure bar, the deformation of this surface after sintering is improved; and by the synergistic effect of the pressure bar constraint and the water and oxygen absorption on the surface of the blank during sintering, the deformation of thin-film cemented carbide is reduced. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0018] Figure 1 This is a schematic diagram of the charging of cemented carbide billets into the furnace according to this application; Figure 2 Image of a cemented carbide sheet sample prepared in Example 1 of this application; Figure 3 Image of the cemented carbide sheet sample prepared in Comparative Example 1 of this application; Wherein: 1-hard alloy blank, 2-pressing strip, 3-groove boat.

[0019] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0020] The technical solutions in the embodiments will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0021] This application discloses a method for suppressing sintering deformation of thin-film cemented carbide, comprising the following steps: S1. Obtain a cemented carbide billet according to the predetermined size, and freeze the cemented carbide billet; Preferably, the cemented carbide blank is placed in an environment of -10~-30℃ and humidity ≤30% for freezing to reduce the overall temperature of the blank to below -10℃. The predetermined dimensions are 10~300mm in length, 10~80mm in width, and 2~15mm in height. The length, width, and height of the cemented carbide blank required are 1.21~1.26 times the predetermined dimensions, respectively.

[0022] S2. Transfer the frozen cemented carbide billet to an environment with room temperature and humidity ≥50% for pretreatment for 10~60min; S3. Place the pretreated cemented carbide blank in a trough-shaped boat and fix it with a pressure bar. Then sinter it to obtain a cemented carbide sheet. Preferred, such as Figure 1As shown, a rectangular cemented carbide blank 1 is placed in a grooved boat 3 and constrained and fixed using a pressure strip 2. In some preferred embodiments of this application, the grooved boat 3 is a V-groove boat with an included angle of 90 degrees, so that both sides of the cemented carbide blank 1 are in close contact with the V-groove. The pressure strip 2 is a high-density graphite strip prepared by cold isostatic pressing, and the surface of the pressure strip 2 is coated with a coating, the main component of which is zirconium oxide or yttrium oxide. The mass of the pressure strip 2 is 20% to 40% of the mass of the cemented carbide blank 1. The sintering temperature is 1420 to 1440°C and the time is 40 to 60 minutes. The cemented carbide sheet obtained by sintering contains 4wt% to 12wt% of the total mass of the cemented carbide blank 1. The cemented carbide sheet contains t% Co, with the balance being WC, additives, and unavoidable impurities. More preferably, the additives may be 0.35wt%~0.25wt% VC and / or 0.25wt%~0.35wt% Cr3C2. The dimensions of the cemented carbide sheet conform to the following: the difference between the length, width, and height and the predetermined dimensions does not exceed 0.5mm, and each surface, when measured with a plug gauge, does not exhibit bending greater than 0.3mm. The performance conforms to the following: cobalt magnetism of 3%~10.5% and magnetic force of 10~45KA / m, and no decarburization occurs. This indicates that the cemented carbide sheet is qualified, and the qualified rate of the cemented carbide sheet obtained by sintering using the method of this application is not less than 98%.

[0023] The technical solution of this application will be further described below with reference to specific embodiments.

[0024] Example 1

[0025] The YG8 grade 120×12×3 cemented carbide is produced. This material is a WC-8%Co cemented carbide with a WC grain size of 1.2~1.6μm and a Co content of 8wt%. The predetermined dimensions are 120mm in length, 12mm in width, and 3mm in height. The production method is as follows: S1. Obtain a cemented carbide blank according to the predetermined size, and freeze the cemented carbide blank in an environment of -10℃ and 20% humidity. The dimensions of the cemented carbide blank are 150±0.2mm in length, 15±0.1mm in width, and 3.7±0.05mm in height. S2. Transfer the frozen cemented carbide billet to an environment with room temperature and 60% humidity for pretreatment for 10 minutes. S3. Place the pretreated cemented carbide blank in a trough-shaped boat and fix it with a pressure strip. Then sinter it at 1440℃ for 60 minutes to obtain cemented carbide sheet. The dimensions of the cemented carbide sheet are 120~120.3mm in length, 12.1~12.25mm in width, and 3.1~3.3mm in height; the cobalt magnetism is 7.7%, and the magnetic force is 11.3KA / m; the maximum bending is 0.2mm when measured with a plug gauge on each side; therefore, the cemented carbide sheet is qualified, and the sample is as follows. Figure 2 As shown.

[0026] A total of 300 cemented carbide sheets were produced using the above method, with a pass rate of 99%.

[0027] Example 2

[0028] The YG8 grade 120×12×3 cemented carbide is produced. This material is a WC-8%Co cemented carbide with a WC grain size of 1.2~1.6μm and a Co content of 8wt%. The predetermined dimensions are 120mm in length, 12mm in width, and 3mm in height. The production method is as follows: S1. Obtain a cemented carbide blank according to the predetermined size, and freeze the cemented carbide blank in an environment of -20℃ and 25% humidity. The dimensions of the cemented carbide blank are 150±0.2mm in length, 15±0.1mm in width, and 3.7±0.05mm in height. S2. Transfer the frozen cemented carbide billet to an environment with room temperature and 55% humidity for pretreatment for 40 minutes. S3. Place the pretreated cemented carbide blank in a trough-shaped boat and fix it with a pressure strip. Then sinter it at 1420℃ for 40 minutes to obtain cemented carbide sheet. The dimensions of the cemented carbide sheet are 120~120.27mm in length, 12.1~12.31mm in width, and 3.1~3.3mm in height; the cobalt magnetism is 7.2%, and the magnetic force is 12.0KA / m; the maximum bending is 0.2mm when measured with a plug gauge on each side; that is, the cemented carbide sheet is qualified.

[0029] A total of 500 cemented carbide sheets were produced using the above method, with a pass rate of 99.2%.

[0030] Example 3

[0031] The YG6X grade 100×15×6 cemented carbide is produced. This material is a WC-6%Co cemented carbide with a WC grain size of 0.6~0.9μm and a Co content of 6wt%. The predetermined dimensions are 100mm in length, 15mm in width, and 6mm in height. The production method is as follows: S1. Obtain a cemented carbide blank according to the predetermined size, and freeze the cemented carbide blank in an environment of -30℃ and 30% humidity. The dimensions of the cemented carbide blank are 124±0.2mm in length, 18.6±0.2mm in width, and 7.4±0.1mm in height. S2. Transfer the frozen cemented carbide billet to an environment with room temperature and 50% humidity for pretreatment for 60 minutes. S3. Place the pretreated cemented carbide blank in a trough-shaped boat and fix it with a pressure strip. Then sinter it at 1430℃ for 50 minutes to obtain cemented carbide sheet. The dimensions of the cemented carbide sheet are 100~100.3mm in length, 15.05~15.41mm in width, and 3~3.36mm in height; the cobalt magnetism is 5.7%, and the magnetic force is 23.4KA / m; the maximum bending is 0.29mm when measured with a plug gauge on each side; that is, the cemented carbide sheet is qualified.

[0032] A total of 600 cemented carbide sheets were produced using the above method, with a pass rate of 98%.

[0033] Comparative Example 1 The difference between this comparative example and Example 1 is as follows: In step S1, the cemented carbide blank is stored in an environment with room temperature and 20% humidity. Step S2 is skipped. In step S3, the material is placed in a flat boat for sintering, and no pressure strips are used to fix it during sintering; The dimensions of the sintered cemented carbide sheets were 119.3–120.7 mm in length, 11.4–12.7 mm in width, and 3–3.4 mm in height, exceeding the standard range; the cobalt magnetism was 7.3%, and the magnetic force was 11.9 KA / m; measurements were taken on all surfaces using a plug gauge, with a maximum side bend of 0.5 mm, indicating significant side bend; the sample... Figure 3 As shown: A total of 300 cemented carbide sheets were produced using the above method, with a pass rate of 70%.

[0034] Comparative Example 2 The difference between this comparative example and Example 1 is as follows: In step S1, the cemented carbide blank is stored in an environment with room temperature and 20% humidity. Step S2 is skipped. In step S3, the material is placed in a trough-shaped boat for sintering, and no pressure strips are used to fix it during sintering; The dimensions of the sintered cemented carbide sheet are 120.3~120.7 mm in length, 12.5~12.7 mm in width, and 3~3.38 mm in height, which are outside the standard range; the cobalt magnetism is 7.3%, and the magnetic force is 11.8 KA / m; the maximum lateral bending is 0.4 mm, measured with a plug gauge on each side. A total of 300 cemented carbide sheets were produced using the above method, with a pass rate of 80%.

[0035] Comparative Example 3 The only difference between this comparative example and Example 1 is that: In step S1, the cemented carbide blank is stored in an environment with room temperature and 20% humidity. The dimensions of the sintered cemented carbide sheet were 119.7~120.4 mm in length, 11.8~12.3 mm in width, and 3~3.3 mm in height; the cobalt magnetism was 7.3%, the magnetic force was 11.9 KA / m, and the maximum bending was 0.32 mm when measured with a plug gauge on each side. Since it was not frozen, the water absorption and oxygen adsorption effect during placement was poor, and the bending on each side was greater than that in Example 1.

[0036] A total of 300 cemented carbide sheets were produced using the above method, with a pass rate of 85%.

[0037] Comparative Example 4 The only difference between this comparative example and Example 1 is that: In step S2, the preprocessing time is 150 minutes; The dimensions of the sintered cemented carbide sheet are 119.5~120.5mm in length, 11.5~12.5mm in width, and 3~3.5mm in height; the cobalt magnetism is 5.8%, and the magnetic force is 15.4KA / m. However, the product undergoes decarburization, so its performance is unqualified. Of the 300 cemented carbide sheets produced using the above method, the pass rate was 0%.

[0038] Comparative Example 5 The only difference between this comparative example and Example 1 is that: Step S2 is skipped. The dimensions of the sintered cemented carbide sheet were 119.7~120.5 mm in length, 12~12.5 mm in width, and 3~3.5 mm in height; the cobalt magnetism was 7.3%, and the magnetic force was 11.9 KA / m; the maximum bending was 0.4 mm when measured with a plug gauge on each surface; since the compact was not placed in a room temperature environment to absorb water and oxygen, the bending on each surface was greater than that in Example 1.

[0039] A total of 300 cemented carbide sheets were produced using the above method, with a pass rate of 82%.

[0040] The above description is only a preferred embodiment of this application and does not limit the patent scope of this application. All equivalent structural transformations made using the content of this application's specification under the inventive concept of this application, or direct / indirect applications in other related technical fields, are included within the patent protection scope of this application.

Claims

1. A method for suppressing sintering deformation of thin-film cemented carbide, characterized in that, Includes the following steps: S1. Obtain a cemented carbide blank according to a predetermined size, and freeze the cemented carbide blank; S2. Transfer the frozen cemented carbide billet to an environment with room temperature and humidity ≥50% for pretreatment for 10~60min; S3. The pretreated cemented carbide blank is placed in a trough-shaped boat and fixed with a pressure bar, and then sintered to obtain a cemented carbide sheet.

2. The method for suppressing sintering deformation of thin-film cemented carbide according to claim 1, characterized in that, The predetermined dimensions are 10-300mm in length, 10-80mm in width, and 2-15mm in height.

3. The method for suppressing sintering deformation of thin-film cemented carbide according to claim 1, characterized in that, In step S1, the cemented carbide blank is placed in an environment of -10~-30℃ and humidity ≤30% for freezing.

4. The method for suppressing sintering deformation of thin-film cemented carbide according to claim 1, characterized in that, The sintering temperature is 1420~1440℃ and the time is 40~60min.

5. The method for suppressing sintering deformation of thin-film cemented carbide according to claim 1, characterized in that, The length, width, and height of the cemented carbide blank are 1.21 to 1.26 times the length, width, and height of the predetermined dimensions, respectively.

6. The method for suppressing sintering deformation of thin-film cemented carbide according to claim 1, characterized in that, The trough-shaped vessel is a V-shaped trough-shaped vessel.

7. The method for suppressing sintering deformation of thin-film cemented carbide according to claim 1, characterized in that, The pressure strip is a graphite strip prepared by cold isostatic pressing, and the surface of the pressure strip is coated with a sprayed coating.

8. The method for suppressing sintering deformation of thin-film cemented carbide according to claim 1, characterized in that, The mass of the pressure strip is 20% to 40% of the mass of the cemented carbide blank.

9. The method for suppressing sintering deformation of thin-film cemented carbide according to claim 1, characterized in that, The cemented carbide sheet comprises 4wt% to 12wt% Co, with the balance being WC, additives, and unavoidable impurities.

10. The method for suppressing sintering deformation of thin-film cemented carbide according to claim 1, characterized in that, The cemented carbide sheet is considered qualified if it meets the following characteristics: The difference between the length, width, and height of the cemented carbide sheet and the predetermined dimensions does not exceed 0.5 mm, and each surface, when measured with a plug gauge, does not exhibit bending greater than 0.3 mm; the cobalt magnetism of the cemented carbide sheet is 3%~10.5%, the magnetic force is 10~45 KA / m, and decarburization does not occur; The pass rate of the cemented carbide sheets shall not be less than 98%.